Ru-catalyzed asymmetric transfer hydrogenation of alpha-acyl butyrolactone via dynamic kinetic resolution: asymmetric synthesis of bis-THF alcohol intermediate of darunavir - More, V. Ganesh; Malekar, V. Pushpa; Kalshetti, Rupali G.; Shinde, Mahesh H.; Ramana, V. Chepuri (Tetrahedron Letters, 2021)
The Ru-catalyzed enantio- and diastereoselective dynamic kinetic resolution of alpha-(benzyloxy/benzoyloxy)acyl-gamma-butyrolactones has been examined via transfer hydrogenation. Employing the in situ prepared (R,R)-Ru-FsDPEN catalyst, the transfer hydrogenation of using formic acid/triethylamine at rt gave the corresponding (S)-3-((S)-2-(benzyloxy/benzoyloxy)-1-hydroxyethyl)dihydrofuran-2(3H)-on e with good to excellent diastereo- and enantioselectivity. One of the resulting hydrogenation product prepared on gram scales was utilized for the synthesis of (3R,3aS,6aR)-hexahydrofuro[2,3-b]furan-3-ol (1), a key synthetic intermediate of various HIV protease inhibitors such as darunavir with excellent enantio-(95% ee) and diastereoselectivities (dr 95:5). (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF-OH intermediate; Darunavir; Dynamic kinetic resolution; Ru-catalysis; transfer hydrogenation